Comportamento e uso de habitat por aves dependentes de áreas úmidas no interior do estado de São Paulo - Cunha, Isabella Lacativa Dias (2014)
The human pressures in aquatics ecosystems are very strong and affect all associated fauna. The waterbirds are a major environmental group in these ecosystems. To April / 2013 until April /2014 were collected the foraging efficiency (FE) of birds in three reservoirs of São Paulo, Itirapina. In the first chapter of this study we tested the hypothesis if the occupation and habitat use for foraging by Herons family are influenced by premises of The Optimal Foraging Theory or that species actively seek for greater energy return and avoid unproductive environments. The central hypothesis was accepted: the species exhibited a similar FE in different macro and micro- habitats; FE does not change regardless of foraging strategy; FE does not depend on the length of stay in the environment. We observed that environmental variables such as the depth of the reservoirs and the surrounding vegetation, may limit the occupation of the habitats for this waterbirds, regardless of the presence and availability of food. In the second chapter, we describe a rare foraging behavior, not yet reported in the literature, displayed by Ardea cocoi in restrictive microhabitat for the species.